Mad, bad & dangerous to know - Ahmed, Samira (Fiction writer) (Soho Teen, 2020)
Told in alternating narratives that bridge centuries, the latest novel from bestselling author Samira Ahmed traces the lives of two young women fighting to write their own stories and escape the pressure of familial burdens and cultural expectations in worlds too long defined by men.